An analysis of the gender determinants of UK graduate migration behaviour - Philip McCann; Stephen Sheppard (European Regional Science Association (ERSA), 2002)
Our paper discusses the relationships between gender, higher education human-capital acquisition and graduate labour mobility. Our analysis is based on a survey of 90,000 students which is examined within the context of of a GIS system. Our results suggest that, in addition to both human-capital and migration-on migration effects, women are more mobile than men. The reasons for this, however, are seen to be related to the differences in the occupational structures of male and female migrants.
Keywords: 330